Auditory Attention Reduced Ear-Canal Noise in Humans by Reducing Subject Motion, Not by Medial Olivocochlear Efferent Inhibition: Implications for Measuring Otoacoustic Emissions During a Behavioral Task - Francis, Nikolas A.; Zhao, Wei; Guinan Jr., John J. (Frontiers in Systems Neuroscience, 2018)
Otoacoustic emissions (OAEs) are often measured to non-invasively determine activation of medial olivocochlear (MOC) efferents in humans. Usually these experiments assume that ear-canal noise remains constant. However, changes in ear-canal noise have been reported in some behavioral experiments. We studied the variability of ear-canal noise in eight subjects who performed a two-interval-forced-choice (2IFC) sound-level-discrimination task on monaural tone pips in masker noise. Ear-canal noise was recorded directly from the unstimulated ear opposite the task ear. Recordings were also made with similar sounds presented, but no task done. In task trials, ear-canal noise was reduced at the time the subject did the discrimination, relative to the ear-canal noise level earlier in the trial. In two subjects, there was a decrease in ear-canal noise, primarily at 1-2 kHz, with a time course similar to that expected from inhibition by MOC activity elicited by the task-ear masker noise. These were the only subjects with spontaneous OAEs (SOAEs). We hypothesize that the SOAEs were inhibited by MOC activity elicited by the task-ear masker. Based on the standard rationale in OAE experiments that large bursts of ear-canal noise are artifacts due to subject movement, ear-canal noise bursts above a sound-level criterion were removed. As the criterion was lowered and more high- and moderate-level ear-canal noise bursts were removed, the reduction in ear-canal noise level at the time of the 2IFC discrimination decreased to almost zero, for the six subjects without SOAEs. This pattern is opposite that expected from MOC-induced inhibition (which is greater on lower-level sounds), but can be explained by the hypothesis that subjects move less and create fewer bursts of ear-canal noise when they concentrate on doing the task. In no-task trials for these six subjects, the ear-canal noise level was little changed throughout the trial. Our results show that measurements of MOC effects on OAEs must measure and account for changes in ear-canal noise, especially in behavioral experiments. The results also provide a novel way of showing the time course of the buildup of attention via the time course of the reduction in ear-canal noise.